Prevalence and antimicrobial resistance patterns of Salmonella isolates in human stools and animal origin foods in Ethiopia: A systematic review and meta-analysis - Abate, Degu; Assefa, Nega (International Journal of Health Sciences, 2020)
Objective: Food-borne diseases caused by non-typhoid Salmonella and the emergences of antimicrobial resistance remains as a public health challenge especially in developing countries. The current study aimed to estimate the pooled prevalence and the antimicrobial resistance patterns of non-typhoid Salmonella in Ethiopia. Methods: Literature search was conducted from major electronic databases and indexing services. Both published and unpublished studies addressing the prevalence and antimicrobial resistance profiles of Salmonella in Ethiopia from 2010-2020 and those studies reported sample size and the numbers of isolates/number of positive samples were included. Data were extracted using format prepared in Microsoft Excel. The identified data were exported to Endnote to remove duplicated studies, then after the remained articles were screened using title, abstract and full text to identify studies that meet the inclusion criteria and finally appraised for methodological validity using JBI guideline. The Pooled prevalence of Salmonella and its drug resistance pattern was computed by a random effects model. I2 test statistic were used to test heterogeneity across studies. The presence of publication bias was evaluated using the Begg's and Egger's tests. Results: A total of 49 eligible articles, 33 of them on human stools, 15 of them on animal origin foods and one both on human stools and animal origin foods were included. The pooled prevalence of Salmonella among human stools and animal origin foods in Ethiopia were 4.8% (95% CI:3.9, 5.9) and 7.7% (95% CI:5.6, 10.4) respectively. The subgroup analysis detected high pooled Prevalence, 7.6 % (95% CI:5.3, 10.7) among outpatients and low, 3.7% (95% CI:2.6, 5.1) in food handlers. The pooled resistant level of Salmonella was 80.6% (95% CI 72.6, 86.7) for ampicillin and 63.5% (95% CI 53.7, 72.4) for tetracycline. Low pooled resistance pattern was reported in ciprofloxacin, 8.7% (95% CI 5.6, 13.3), and ceftriaxone 12.2% (95% CI 7.9, 18.3). There was some sort of publication bias. Conclusion: High pooled prevalence of Salmonella among human stools and animal origin foods which were 4.8% and 7.7% respectively, and high Salmonella resistance, greater than 72% to ampicillin and tetracycline were detected in Ethiopia. Antimicrobial stewardship efforts and infection control strategies are required to mitigate this major public health concern.